SiNPs induce ferroptosis in HUVECs through p38 inhibiting NrF2 pathway - Jiang, Xiaojun; Gao, Huiqian; Cao, Yunchang; Chen, Shuting; Huang, Fangfang; Feng, Yashi; Zhang, Yuqi; Feng, Shaolong (Frontiers in Public Health, 2023)
Despite of growing evidence linking silica nanoparticles (SiNPs), one of the global-top-three-produced and -used nanoparticle (NP), to human health risks, there remain many knowledge gaps over the adverse effects of SiNPs exposure on cardiovascular system and the underlying molecular mechanisms. In this study, the ferroptotic effects of SiNPs (20 nm; 0, 25, 50, 100 µg/mL) on human umbilical vein endothelial cells (HUVECs) and the possible molecular mechanism were studied. The results showed that at the tested concentrations, SiNPs could decrease HUVEC viability, but the deferoxamine mesylate (an iron ion chelator) might rescue this reduction of cell viability. Also, increased levels of intracellular reactive oxygen species and enhanced mRNA expression of lipid oxidation enzymes (ACSL4 and LPCAT3) with increase in lipid peroxidation (malondialdehyde), but decreased ratios of intracellular GSH/total-GSH and mitochondrial membrane potential as well as reduced enzymatic activities of anti-oxidative enzymes (CAT, SOD, and GSH-PX), were found in the SiNPs-treated HUVECs. Meanwhile, increase in p38 protein phosphorylation and decrease in NrF2 protein phosphorylation with reduced mRNA expressions of downstream anti-oxidative enzyme genes (CAT, SOD1, GSH-PX, and GPX4) was identified in the SiNPs-exposed HUVECs. These data indicated that SiNPs exposure might induce ferroptosis in HUVECs via p38 inhibiting NrF2 pathway. Ferroptosis of HUVECs will become a useful biomarker for assessing the cardiovascular health risks of environmental contaminants.